The growth drivers : the definitive guide to building marketing capabilities - Bird, Andy; McEwan, Mhairi (Hoboken, NJ : Wiley, 2011)
'The Growth Drivers is not only a practical guide to building marketing capabilities it explains why it is critical that organisations invest in the capabilities needed to excel at customer-centric marketing to drive growth'--
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / Marketing / General; Market segmentation; Economic development; Investments